SAT0387 Anti Tnf Treatment of Reactive Arthritis. A Monocentric Experience. (15th July 2016) - Brinster, A.; Guillot, X.; Prati, C.; Wendling, D.
Abstract : Background: Reactive arthritis is still a matter of interest and a current problem, since its treatment is not standardized, with the possibility of a chronic evolution. Nevertheless, anti TNF agents may be of interest, as illustrated by small multicentric series. Objectives: To evaluate efficacy and safety of anti TNF agents in the treatment of patients with reactive arthritis followed in a single center. Methods: We analyzed retrospectively the data of patients with reactive arthritis, according to proposed criteria treated with TNF blockers, from July 2007 to December 2013 in an University Hospital in France. Results: Over this period, 31 cases of Reactive arthritis were followed in our department, of whom 15 (48%) received at least one dose of anti TNF. They are in majority male (n=13), mean age 35 years, 66% HLA-B27 positive. Evidence of infection was found in 9/15 patients (4 Chlamydia). After failure of NSAIDs, steroids and conventional DMARDs, anti TNF agents were introduced with a median delay of 116 days after onset of rheumatic symptoms: etanercept (ETN) 9 cases, infliximab (IFX) and adalimumab (ADA) (3 cases each) (Table). The clinical improvement was rapid, all the patients developed a clinical response to anti TNF therapy which could be stopped in 5 cases: 3 IFX after a mean of 4.6 infusions, 2 ETN after 4 and 10 months. Eight patients developed chronic spondyloarthritis, and one psoriatic arthritis, with a mean follow-up of 4.8 years, and requiring anti TNF continuation. The last patient was lost in follow-up. The treatment was well tolerated, with a mean exposition duration of 34 months by patient, neither serious infection nor reactivation of the triggering infection was recorded. Compared to the patients with reactive arthritis not treated with anti TNF over the same period, we found no differences regarding clinical data (age, arthritis distribution, type of initial infection), biologic data (CRP, HLA-B27 positivity, evidence of infectious agent). Dactylitis were more frequent (although not significant) in patients treated with anti TNF agents (40% vs 20%). In the same way, there were no differences between the patients who could stop anti TNF after several months, due to remission, and those for whom continuation was necessary, except a shorter median delay of initiation of the TNF blocker: 44 days versus 173 days respectively. Conclusions: Anti TNF therapy for reactive arthritis seems to be associated with symptomatic efficacy and good tolerance with the possibility, in one third of the cases of short lasting treatment leading to remission, which seems associated to the precocity of anti TNF initiation, suggesting a kind of window of opportunity in this subset of spondyloarthritis. However, the impact of this treatment upon the outcome of the disease needs to be further evaluated. Disclosure of Interest: None declared